2021
DOI: 10.3390/antiox10081303
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of Radical Inactivation, LOX Inhibition, and Iron Chelation: The Role of Ferulic Acid in Skin Protection against UVA Induced Oxidative Stress

Abstract: Ferulic acid (FA) is used in skin formulations for protection against the damaging actions of the reactive oxygen species (ROS) produced by UVA radiation. Possible underlying protective mechanisms are not fully elucidated. By considering the kinetics of proton-coupled electron transfer (PCET) and radical-radical coupling (RRC) mechanisms, it appears that direct scavenging could be operative, providing that a high local concentration of FA is present at the place of •OH generation. The resulting FA phenoxyl rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 75 publications
0
13
0
Order By: Relevance
“…As a potent LOX inhibitor, CA was previously reported to prevent H 2 O 2 ‐ and nonsteroidal anti‐inflammatory drug‐induced programmed cell death 54,55 . FA is also described as a LOX inhibitor in previous reports 56,57 . To explore the role of LOX inhibition in pyroptosis and the connection between the anti‐pyroptotic and anti‐LOX activity of CA, we employed another LOX inhibitor, Zileuton 58 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a potent LOX inhibitor, CA was previously reported to prevent H 2 O 2 ‐ and nonsteroidal anti‐inflammatory drug‐induced programmed cell death 54,55 . FA is also described as a LOX inhibitor in previous reports 56,57 . To explore the role of LOX inhibition in pyroptosis and the connection between the anti‐pyroptotic and anti‐LOX activity of CA, we employed another LOX inhibitor, Zileuton 58 .…”
Section: Discussionmentioning
confidence: 99%
“…54,55 FA is also described as a LOX inhibitor in previous reports. 56,57 To explore the role of LOX inhibition in pyroptosis and the connection between the anti-pyroptotic and anti-LOX activity of CA, we employed another LOX inhibitor, Zileuton. 58 We found that 12.5-50 µM Zileuton failed to suppress the LPS/Nigericininduced release of LDH.…”
Section: Discussionmentioning
confidence: 99%
“…Ferulic acid is promptly absorbed by the skin when topically applied and protects the skin from UVB radiation-induced skin erythema and pigmentation in cells from human breast reduction surgeries [ 85 ]. Docking studies indicated that ferulic acid and its derivative, 5-hydroxyferulic acid, interact with the active site of the lipoxygenase (LOX) enzyme, with a consequent inhibition of its activity, representing a potential mechanism of skin protection against UV radiation-induced oxidative stress [ 86 ]. Recently, ferulic acid was also evaluated in an elegant split-face comparative study, alone or associated with microneedling [ 25 ].…”
Section: Promising Natural Compounds and Herbal Preparation For The D...mentioning
confidence: 99%
“…Oxidative stress is a key factor in epidermal barrier disruption, skin ageing, and melanogenesis, despite ROS's importance in biological signalling systems. Triggers of oxidative stress in the environment, such as ultraviolet (UV) radiation and visible light, both affect skin parameters in similar ways, resulting in compromised skin barrier function and cosmetically unattractive hyperpigmentation [121,122,123].…”
Section: Natural Anti-oxidant For Skin Carementioning
confidence: 99%